A. \(z = 3 + \sqrt 2 i\).
B. \(z = 3 - \sqrt 2 i\).
C. \(\left[ \begin{array}{l}z = 3 + \sqrt 2 i\\z = 3 - \sqrt 2 i\end{array} \right.\).
D. Một kết quả khác.
C
\(\begin{array}{l}{z^2} - 6z + 11 = 0\\ \Leftrightarrow \left( {{z^2} - 6z + 9} \right) + 2 = 0\\ \Leftrightarrow {(z - 3)^2} + 2 = 0\\ \Rightarrow \left[ \begin{array}{l}z - 3 = i\sqrt 2 \\z - 3 = - i\sqrt 2 \end{array} \right. \Leftrightarrow \left[ \begin{array}{l}z = 3 + i\sqrt 2 \\z = 3 - i\sqrt 2 \end{array} \right.\end{array}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247